La vertiente - Soria Gamarra, Oscar, 1917-1988; Río, Rosario del; Vaca Pereyra, Raúl (Instituto Cinematográfico Boliviano, 1958)
An alligator hunter falls in love with a teacher from the West. Rurrenabaque, the town where the story takes place, is at the crossroads of collaborating in the installation of the drinking water system or following the tradition of "drinking water from the river." Ruiz uses a historical fact to tell (combining his skill as a documentary filmmaker) a love story. --